PENGARUH VIDEO EDUKASI TERHADAP PENGETAHUAN IBU-IBU PKK PESERTA JKN-KIS TENTANG PROGRAM JKN DI DESA TIRTOMOYO - DEA RIRA PANDUWINATA; AAI CITRA DEWIYANI; ANGGI ARDHIARTI (Program Studi Pendidikan Informatika, Universitas Citra Bangsa, 2023)
In Tirtomoyo Village there are still many residents who do not know about the JKN program, as evidenced by the results of a preliminary survey conducted by researchers of 25 people, 21 people did not know about the JKN program and 4 others already knew about the program. This study aimed to determine the knowledge level of PKK women participating in JKN-KIS before and after giving educational videos about JKN in Tirtomoyo Village. The object of this study was 30 respondents from members of the PKK participating in JKN-KIS. Data collection techniques by filling out the PreTest PostTest questionnaire. The results of the research value (P-Value 0.000) mean that there is a difference in the knowledge of PKK women participating in JKN-KIS about the JKN program in Tirtomoyo Village before and after being given the educational video. The conclusion from this study is that providing educational videos on the knowledge of PKK women participating in JKN-KIS about the JKN program in Tirtomoyo Village has an effect.